Contractual savings institutions and banks' stability and efficiency - Impavido, Gregorio (Policy research working paper, 2001)
This paper argues that contractual savings (assets of pension funds and life insurance companies) contribute to the improvemnet of banks' efficiency, credit, and liquidity risk. The authors use bank level panel data across countries to assess the impact of contractual savings on bank efficiency and lending behavior. They concentrate on profitability measures and on transformation and credit risk indicators